2009
DOI: 10.1002/dc.20997
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial inclusion cyst arising in an intramammary lymph node: Case report with cytologic findings

Abstract: The occurrence of epithelial inclusion cysts (EIC) in axillary lymph nodes is a rare but well recognized entity, arising either from direct implantation or from embryonal rests. Theoretically, EIC can occur in intramammary lymph nodes, but there has been only one prior report of such a lesion. Here, we describe a case of an EIC arising in an intramammary lymph node of a 37-year-old woman. This report focuses on the FNA cytologic features of this lesion and its differential diagnoses. On FNA, the EIC arising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Heterotopic epithelial inclusions in lymph nodes have been identified in multiple anatomical sites; however, except for the axillary region, which has a high number of cases, all other anatomical regions have been reported as single cases ( 2 , 4 , 5 , 9 , 10 ). The most concerning aspect of benign epithelial inclusions in lymph nodes is that they may be misinterpreted as tumor metastases ( 1 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotopic epithelial inclusions in lymph nodes have been identified in multiple anatomical sites; however, except for the axillary region, which has a high number of cases, all other anatomical regions have been reported as single cases ( 2 , 4 , 5 , 9 , 10 ). The most concerning aspect of benign epithelial inclusions in lymph nodes is that they may be misinterpreted as tumor metastases ( 1 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no ultrasonographic descriptions of heterotopic squamous epithelial inclusion cysts in cervical lymph nodes have been provided in the literature, and there have only been a few reports of these cysts in other anatomical sites. Nakaguro et al ( 9 ) reported an echogenic solid tumor, with well-defined edges, in the right breast. Kim et al ( 10 ) reported a hypoechoic mass in the celiac region.…”
Section: Discussionmentioning
confidence: 99%